UNITED STATES AND IRAN INTERVENTION IN THE POST-ARAB SPRING CONFLICT IN YEMEN - Ahmad Zainal Mustofa; Magdy B. Behman (Arabic Literature Department, 2022)
This article describes the involvement of the United States and Iran in the conflict that occurred in Yemen after the Arab Spring. The conflict occurred due to political turmoil between the government and the opposition, in which America is a supporter of the government regime along with their ally, namely Saudi Arabia. In the opposition camp, Iran gave their support to the Houthi group that had the same ideology, namely Shi'ah. This research was conducted to answer the question of what are the interests of the United States and Iran in the proxy war in Yemen? The theory used in this research is the concept of national interest. This concept is closely related to the view of realism in international relations. The research method used is descriptive analytical by analyzing the relevant variables from various sources that have been filtered according to research needs. After conducting research, it can be concluded that the involvement of the United States and Iran in the Yemen conflict can be seen from four factors of national interest, namely defense interests, economic interests, world order interests, and ideological interests. Of these four interests, both the US and Iran want to show their dominance, existence, strength and influence in global politics of eyes world through intervention in the Yemen conflict after the Arab Spring.